Pengembangan Cagar Budaya Wisata Religi Asta Tinggi Dalam Meningkatkan Potensi Pariwisata Di Kabupaten Sumenep - Farhana Risqi Laily; Ida Syafriyani (FISIP UWP, 2022)
Asta Tinggi as one of the heritage of the cultural heritage in Sumenep, is one of the popular religious tourism in the eyes of the local community. Asta Tinggi is the tomb building of the kings of Sumenep and his descendants. The problem in Asta Tinggi is the problem of facilities that are still inadequate to support the needs of tourists, so it takes the development of Asta Tinggi for the success of a tourist destination. This research uses qualitative descriptive methods. The results of this study refer to the focus of research with 3 indicators of success of tourism development according to Yoeti (2008: 96) namely (1) The presence of Attractions and Attractions, this has been done with the existence of tourist attractions carried out by Disparbudpora Kab Sumenep in attracting outside tourists to visit Asta Tinggi. (2) Accessibility, tourists who visit alone can take advantage of gojek to go to Asta Tinggi, and the Sumenep government has also provided 145 guides that are licensed. (3) The existence of facilities, building improvements and fulfillment of facilities that are still felt lacking. Therefore, the conclusion that the Development of Religious Tourism Cultural Heritage asta Tinggi with the promotion of tourism that can be through the Internet media to introduce tourist products, Accessibility is important to be developed as an ease of access for tourists. The advice that can be given is expected to be cooperation between the Sumenep Regency government and the management of Asta Tinggi.